2022
DOI: 10.1136/tsaco-2021-000876
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors associated with helmet use in pediatric ATV and dirt bike trauma

Abstract: ObjectivesRecreational off-road vehicle crashes can produce severe injury and death among children, often from head trauma sustained while riding unhelmeted. Although required for competition, recreational riders commonly forego helmets. This study aimed to identify socioeconomic factors associated with unhelmeted injuries among children riding all-terrain vehicles (ATVs) and dirt bikes recreationally, thus informing injury prevention efforts.MethodsA retrospective review was completed of patients younger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…The unhelmeted riders had a higher ISS compared to helmeted riders. This is consistent with our study that demonstrates that most patients in our cohort did not wear helmets [11]. However, we did not find a significant difference in ISS between helmeted versus unhelmeted patients.…”
Section: Discussionsupporting
confidence: 93%
“…The unhelmeted riders had a higher ISS compared to helmeted riders. This is consistent with our study that demonstrates that most patients in our cohort did not wear helmets [11]. However, we did not find a significant difference in ISS between helmeted versus unhelmeted patients.…”
Section: Discussionsupporting
confidence: 93%
“…A study done on crash injuries in children 18 years and younger who rode bicycles and ATVs reported that residence in a county with both lower median income and scholastic graduation rates associated were associated with unhelmeted crashes, and lower median income signi cantly predicted unhelmeted crashes. This study revealed socioeconomic factors that identify communities with greatest need for injury prevention initiatives [23]. A study done in Bangladesh by Tana et al found a 1.17 times (95% CI 1.02-1.35; p 0.03) higher risk of head injuries in road tra c accidents, in the unhelmeted group compared to the helmeted group [24].…”
Section: Discussionmentioning
confidence: 76%
“…A study done on crash injuries in children 18 years and younger who rode bicycles and ATVs reported that residence in a county with both lower median income and scholastic graduation rates associated were associated with unhelmeted crashes, and lower median income signi cantly predicted unhelmeted crashes. This study revealed socioeconomic factors that identify communities with greatest need for injury prevention initiatives [24]. A study done in Bangladesh by Tana et al found a 1.17 times (95% CI 1.02-1.35; p 0.03) higher risk of head injuries in road tra c accidents, in the unhelmeted group compared to the helmeted group [25].…”
Section: Discussionmentioning
confidence: 76%